Film Horor Sebuah Definisi yang Berubah - Yoesoef, M. (UI Scholars Hub, 2003)
Horror film is a film genre that presents things that are frightening, tense, and horrifying. The idea of horror film is basically to terrorize the audience through various terrifying acts or actors. Horror films in the beginning are closely related to stories rooted in the cultural of Europe, especially English literature. The definition of horror in the beginning was a story that presented uncomfortable feelings to the readers. This definition changed with the development of film. Horror film developed into a genre that came to stand side by side with drama, comedy film, gangster film, and action film.